Implementasi Moderasi Beragama Melalui Pendekatan Kognitif Berbasis Karakter: Implementation of Religious Moderation Through Character-Based Cognitive Approach - Thobib asyhar (Direktorat Jenderal Bimbingan Masyarakat Islam, 2023)
Religious moderation practice in pluralistic societies such as Indonesia is a historical necessity. This nation would never have stood without the implementation of religious moderation by the founding fathers who have been fighting since the pre-independence era. In this article, the author focuses on the urgency of implementing religious moderation through a character-based cognitive approach. The writing method employs a descriptive-analytical approach to the cognitive elements that strongly support the implementation of religious moderation, using the revised Bloom's Taxonomy theory: remember, understand, applying, analyze, evaluate, and create. Meanwhile, the character basis emphasizes three main attitudes and behaviors: open-mindedness, acceptance, and cooperation towards individuals or parties who are different, in beliefs, religious ideologies, and religions. The conclusion of this writing is that the practice of religious moderation is believed to be more effective when supported by the quality of cognitive aspects, enabling religious communities to have adequate insight based on character development through the cultivation of values such as honesty, fairness, balance and responsbility.